2007
DOI: 10.1037/0022-3514.93.4.544
|View full text |Cite
|
Sign up to set email alerts
|

Mere effort and stereotype threat performance effects.

Abstract: Although the fact that stereotype threat impacts performance is well established, the underlying process(es) is(are) not clear. Recently, T. Schmader and M. Johns (2003) argued for a working memory interference account, which proposes that performance suffers because cognitive resources are expended on processing information associated with negative stereotypes. The antisaccade task provides a vehicle to test this account because optimal performance requires working memory resources to inhibit the tendency to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
284
12
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(325 citation statements)
references
References 78 publications
24
284
12
4
Order By: Relevance
“…Although we believe that these findings shed light on the component processes involved in working memory impairments, Jamieson and Harkins (2007) interpreted their results as being incompatible with the idea that stereotype threat affects working memory. In their view, stereotype threat motivates mere effort at the task, which then leads to an increased potentiation of a prepotent response.…”
Section: Do Individual Differences In Working Memory Moderate Stereotmentioning
confidence: 59%
See 2 more Smart Citations
“…Although we believe that these findings shed light on the component processes involved in working memory impairments, Jamieson and Harkins (2007) interpreted their results as being incompatible with the idea that stereotype threat affects working memory. In their view, stereotype threat motivates mere effort at the task, which then leads to an increased potentiation of a prepotent response.…”
Section: Do Individual Differences In Working Memory Moderate Stereotmentioning
confidence: 59%
“…Spencer et al, 1999) and more subtle manipulations in which the researcher's expectations for poor performance are less likely to be consciously primed (e.g., Inzlicht & Ben-Zeev, 2000; J. L. Smith & White, 2002;Stone & McWhinnie, in press). Furthermore, recent evidence confirms that such manipulations increase one's motivation to try to disconfirm the negative stereotype, at least for those who are highly identified with the domain (Forbes, Schmader, & Allen, 2007;Jamieson & Harkins, 2007). Some have suggested that stereotype threat has little impact outside of the laboratory (Cullen, Hardison, & Sackett, 2004;Stricker & Ward, 2004).…”
Section: A Primer On Stereotype Threatmentioning
confidence: 99%
See 1 more Smart Citation
“…Past research with college students has suggested that to be impacted by stereotype threat, women must be identified with mathematics and take a difficult mathematics test in an evaluative situation in which their gender is made salient. Steele (1997) proposed that stereotype threat affects people who identify with the domain in question (in this case, women who are identified with mathematics; Forbes, Schmader, & Allen, 2008;Jamieson & Harkins, 2007;Smith & White, 2001). Mathematics identification involves two components: feeling that you are good at mathematics and feeling that it is important to you to be good at mathematics (Smith & White, 2001).…”
Section: Conditions Under Which Stereotype Threat Effects Occurmentioning
confidence: 99%
“…Here, research shows that the situational salience of a negative stereotype may deplete working memory efficiency to bring about performance decrements on a given task (Schmader & Johns, 2003). Conversely, other researchers have argue that the experience of stereotype threat may motivate individuals to disprove the negative stereotype, thus influencing goal engagement and enhanced control (Jamieson & Harkins, 2007).…”
Section: Stereotype Threat and Inhibitory Controlmentioning
confidence: 99%